Development Of Quizlet-Based Interactive Flash Card Media For Teaching Arabic Vocabulary In The Sixth Grade Of MI Ihyauudiniyah - LM. Vaida; Isnul Khotimah (EL-IBTIKAR: Jurnal Pendidikan Bahasa Arab, 2026)
Quizlet-based flashcards are an interactive learning medium that can be used to improve students' understanding of Arabic vocabulary (mufrodat). This study aims to develop and evaluate the effectiveness of using Quizlet-based flashcards in teaching mufrodat in the sixth grade at MI Ihyauddiniyah. The media developed are digital flashcards that utilise the interactive features of the Quizlet platform. The approach used is qualitative with a research and development (R&D) type of study using the ADDIE [Analysis, Design, Development, Implementation, Evaluation] development model, involving 15 sixth-grade students and one Arabic teacher at MI Ihyauddiniyah Duren as research subjects. Data was collected through interviews, observations, and questionnaires. The results of the study indicate that the use of Quizlet-based Flash Cards requires innovative media to increase students' interest and motivation to learn. Quizlet-based flashcards were successfully developed with features such as flashcards, learn, write, match, test, and validation results from media and material experts show that it is suitable for use. Its implementation in the classroom shows an increase in student enthusiasm and active participation  in learning, and this media has succeeded in helping and facilitating them in memorising and mastering Arabic vocabulary. Most students feel more interested and involved in learning because of Quizlet's interactive features, such as games and quizzes that support material repetition. In addition, teachers also responded positively to the use of this media in learning, as it can increase classroom dynamics and student engagement. Based on these findings, it can be concluded that Quizlet-based flashcards are an effective medium for improving vocabulary mastery in Arabic language learning.